Free access to multilingual digital books: a tool to increase book reading? - Bus, Adriana G.; Broekhof, Kees; Vaessen, Karin (Frontiers in Education, 2023)
The objective of the study was to examine how providing access to multilingual digital picture books affected the reading habits and language development of children from bilingual families. The study included 41 children aged 4–5 from two schools whose parents spoke a heritage language distinct from the environmental language (Dutch), and had a low level of education. The children were randomly assigned to two groups - one with access to digital books solely in the environmental language (Dutch) and the other with a choice between the environmental language and their heritage language. A general vocabulary test was administered before and after a six-week intervention period. The findings indicated that access to digital books motivated reading, with roughly one-third of the children reading a substantial number of books during the intervention. The availability of books in the heritage language did not lead to an increase in book reading. Given a choice, only a minority (33%) preferred to read in their heritage language. The conditions exhibited similar growth in vocabulary, but the study uncovered positive associations between the number of books and vocabulary development.